Influence of Strategic Communication on Growth of Students’ Population in Selected Private Universities in Kenya - Joseph Kiprono Yegon (International Journal of Engineering and Management Research, 2019)
The study sought to investigate the influence of strategic communication on the growth of students’ population in selected private universities in Kenya. The study was guided by resource-based theory. The study utilized descriptive research design. Random sampling technique was used to select research respondents. The study targeted private universities in north rift, south rift and Nyanza region of Kenya. The unit of observations was staff and students in various departments and faculties existing in the institutions. The study used purposive sampling to select research respondents. Questionnaire was the main instrument for data collection. Descriptive and inferential statistics with the aid of SPSS version 23.0 were used to analyze collected data and presented using frequency distribution tables and bar graphs. The findings indicated that if strategic communication is changed by one unit, the growth of student population will increase by a margin of 0.440. The study concludes that strategic communication plays a critical role in growing students’ population in private universities. It is also recommended that private universities should consider using professional bloggers to build the publicity of the institution. Top management of the private universities will get insight on various strategic issues with regard to student population through the recommendations of the study. Scholars in the field of strategic management will find the study useful as it will form basis of future references.